Michał Kalecki o planowaniu i rozwoju w krajach ekonomicznie słabo rozwiniętych - Gołębiowski, Ryszard (Wydział Prawa i Administracji UAM, 1974)
Summarizing, the author has stated that Michał Kalecki stresses the complex aim synchronization of plans by means and possibilities of its realization, the intitutional factors including. In his opinion almost all the people should participate in the benefits of economic planning. All difficulties and barriers should be taken into consideration while the plan is being worked out. He has also shown that in this way it is possible to gain serious economic results without any assistance of foreign countries. However, this is only possible to achieve on the way of effective planning, proper organization and economic management.
M. Kalecki's Theory of Planning and Economic Growth in the Developing Countries